Organic electrochromic energy storage materials and device design - Liu, Qingjiang; Yang, Liangliang; Ling, Wei; Guo, Binbin; Chen, Lina; Wang, Jiaqi; Zhang, Jiaolong; Wang, Wenhui; Mo, Funian (Frontiers in Chemistry, 2022)
While not affecting electrochemical performance of energy storage devices, integrating multi-functional properties such as electrochromic functions into energy storage devices can effectively promote the development of multifunctional devices. Compared with inorganic electrochromic materials, organic materials possess the significant advantages of facile preparation, low cost, and large color contrast. Specifically, most polymer materials show excellent electrochemical properties, which can be widely used in the design and development of energy storage devices. In this article, we focus on the application of organic electrochromic materials in energy storage devices. The working mechanisms, electrochemical performance of different types of organics as well as the shortcomings of organic electrochromic materials in related devices are discussed in detail.